Melaleuca alternifolia Essential Oil against the Lesser Mealworm (Alphitobius diaperinus) and Its Possible Effect on the Soil Fauna - Volpato,A (2016)
ABSTRACT The aim of this study was to evaluate the in vitro bioactivity of tea tree (Melaleuca alternifolia) essential oil against larvae and adult forms of lesser mealworms (Alphitobius diaperinus) and its influence on the soil fauna. Tests were performed in triplicate using pure tea tree oil (TTO; 1, 5, 10, 25, 50, and 100%), TTO nanoparticles (1, 3, and 7.5%), or terpinen-4-ol, the main compound of the tea tree oil, at the same concentrations of TTO. Larvae and adult mortality occurred at concentrations up to 10 and 50% of TTO, respectively. No larvicidal or insecticidal effect of TTO nanoparticles was observed. Terpinen-4-ol showed insecticidal and larvicidal effect at concentrations higher than 25%. The evaluation of TTO effect on soil organisms was performed by standard ecotoxicological tests (ISO) with the springtail species Folsomia candida. Only TTO was used for ecotoxicological tests in doses of 1, 5, 10, 25, 50, and 100 mg kg-1 of soil. TTO had no negative effects on F. candida survival or reproduction. Therefore, it was concluded that M. alternifolia oil may be a new alternative for control of the lesser mealworm.